2022
DOI: 10.3389/fgene.2022.979377
|View full text |Cite
|
Sign up to set email alerts
|

Case report: Rare among ultrarare—Clinical odyssey of a new patient with Ogden syndrome

Abstract: Introduction: The definition of ultra-rare disease in terms of its prevalence varies between the sources, usually amounting to ca. 1 in 1.000.000 births. Nonetheless, there are even less frequent disorders, such as Ogden syndrome, which up to this day was diagnosed in less than 10 patients worldwide. They present typically with a variety of developmental defects, including postnatal growth retardation, psychomotor delay and hypotonia. This disorder is caused by the heterozygous mutations in NAA10 gene, which e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…The underlying genetic defect was characterized as a single missense change coding for Ser37Pro in the X-linked gene, NAA10 , and was confirmed in a second independent family in California, USA, with three males that also died during infancy. The identical variant was recently reported in a third family [ 28 ], and a fourth family [ 29 ]. There is a S .…”
Section: Introductionsupporting
confidence: 59%
“…The underlying genetic defect was characterized as a single missense change coding for Ser37Pro in the X-linked gene, NAA10 , and was confirmed in a second independent family in California, USA, with three males that also died during infancy. The identical variant was recently reported in a third family [ 28 ], and a fourth family [ 29 ]. There is a S .…”
Section: Introductionsupporting
confidence: 59%
“…A total of 170 articles were included in the final review (alphabetically ordered based on author in Supplementary Table 2). 1,2,7–50,55,56,68–189 A PRISMA flow diagram is presented to track the process and number of studies included and excluded (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Ogden syndrome (OMIM: 300855) is a lethal X‐linked disorder caused by a missense mutation in the NAA10 gene, encoding the catalytic subunit of the NatA complex. So far, the syndrome has been detected in 10 boys from four families, all presenting with distinct aged appearance, craniofacial anomalies, developmental delay, congenital heart defects, cardiac arrhythmias, and cardiomegaly (Gogoll et al, 2021; Hofman et al, 2022; Rope et al, 2011). Biochemical and cellular studies in yeast and patient cells suggested NatA‐mediated Nt‐acetylation deficiency as a cause of disease etiology (Myklebust et al, 2015).…”
Section: Discussionmentioning
confidence: 99%